Fire performance assessment of six Malaysian wood species for furniture applications - Ali, Suhaila (2021)
The main objective of this research is to determine the HRR of fire in compartments containing Malaysian wooden furniture. Thus, this work decided on an appropriate fire model to simulate the designated fire scenario as well as necessary bench-scale tests to evaluate the fire properties of selected wood species for use as input data in the fire model. Since this work is the first of its kind, six species of untreated Malaysian wood have been selected for this research; Shorea-laevis, Vatica-rassak, Koompassia-malaccensis, Heritiera-albiflora, Shorea-parvifolia, and Cratoxylum-arborescens. The cone calorimeter testing, the bomb calorimeter testing, and the thermogravimetric analysis were bench-scale tests used to quantify the fire properties of the wood. In addition, the Coats and Redfern method was used to determine the pyrolysis kinetics of the wood. While the B-RISK fire simulation software was used to simulate the designated fire scenario. The result of the cone calorimeter test shows that the Vatica-rassak is recognised to be the most resistant in the fire resistance assessment of ignition time, critical heat flux, and ignition temperature from the perspective of relative performance. In relation to the amount of energy released during the combustion of one mole of a substance in the bomb calorimeter test, the range of energy released for the six untreated wood is between 31.10 and 35.96 kJ/g. From the thermogravimetric analysis, the wood encountered moisture dehydration up to ~ 170°C. Followed by the second stage of decomposition, between 170 - 510°C, and the third stage of decomposition occurred between 380 - 740°C. The maximum decomposition for each wood was observed to occur at the peak temperature, and as the heating rate increased, the maximum decomposition for all wood shifted to a higher temperature. The wood's pyrolysis kinetics analysis showed that the second stage of decomposition requires more activation energy (Ea) than the third stage. The Ea is the minimum amount of energy that molecules need to cause a reaction or begin to break bonds. In the heavy hardwood category, Vatica-rassak was found to have a higher Ea than Shorea-laevis, while in the medium hardwood category, Heritiera-albiflora was found to have a higher Ea than Koompassia-malaccensis. In the light hardwood category, Cratoxylum-arborescens requires more Ea than Shorea-parvifolia. These bench-scale test results are then used as input data in B-RISK version 2019.03, an open-source fire model software. Six fire scenarios were designed and developed in the B-RISK fire model software, each with 1000 iterations, featuring an office with 14 common office furniture and electrical appliances including a wooden table, two wooden cabinets, and a wooden drawer. According to the fire simulation, the Vatica-rassak is the best choice for making high-end office furniture since it contributes to the lowest total heat release. The performance-based method applied in this study has successfully provided the best option for fire assessment in a compartment equipped with wooden furniture in a limited time and at a low cost.